Preparation method and application of printable mesoporous perovskite solar cell without high-temperature heat treatment
By using a printable method without high-temperature heat treatment in the preparation of perovskite solar cells, the mixed slurry of perovskite precursor solution and functional materials for low-temperature drying and film formation, the high-temperature heat treatment in the prior art is solved. High energy consumption and device defect problems have achieved efficient and low-cost large-area battery preparation.
Patent Information
- Application Number
- CN202411486043.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing mesoporous perovskite solar cell preparation process requires multiple high-temperature heat treatments, resulting in complex equipment, high energy consumption, easy-to-defects in devices, and is not conducive to the production of large-area battery modules.
By using the printing mesoporous perovskite solar cell preparation method without high temperature heat treatment, the perovskite-electron transport material, perovskite-insulating material, perovskite-bottom electrode material and perovskite precursor solution , thickener is added to adjust the viscosity and leveling, and applied to the conductive substrate in turn, and film formation of the functional layer and crystallization of perovskite are achieved by low temperature drying.
This method reduces heat treatment requirements, reduces energy consumption and cost, reduces defects in the device, improves the photoelectric conversion efficiency of the battery, and is suitable for the preparation of large-area perovskite solar cells.
Smart Images

Figure CN119451523A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solar cells, and more specifically, relates to a method for preparing a printable mesoporous perovskite solar cell without high-temperature heat treatment and its application. Background Art
[0002] Solar photovoltaic power generation is recognized as a clean, pollution-free, low-cost, and renewable power generation technology. Traditional silicon-based batteries have low theoretical efficiency, and there are problems such as complex production processes, high energy consumption, and large fluctuations in the industrial chain. The development of a new generation of solar photovoltaic cells is urgent. Perovskite solar cells have the advantages of high theoretical capacity, simple production processes, and low costs, and have made great progress in recent years. Perovskite solar cells can be mainly divided into planar configurations and mesoporous configurations. The planar configuration refers to a battery configuration in which all functional layers are dense planar shapes, and the mesoporous configuration refers to a battery configuration in which at least one charge transport layer (electron transport layer or hole transport layer) is a mesoporous structure. Due to the large specific surface area and small pore size of the charge transport layer-perovskite interface of the mesoporous configuration, the transmission distance of photogenerated electrons and holes in the perovskite is reduced, the selective extraction efficiency of the charge transport layer for electrons or holes is improved, and the recombination of photogenerated carriers is suppressed, which has a significant effect on improving the efficiency of the device.
[0003] In the past, the preparation process of mesoporous perovskite solar cells was generally carried out by multiple coating and heat treatment methods. For example, the typical preparation process of perovskite solar cells based on mesoporous TiO2 electron transport layer includes coating mesoporous TiO2 slurry, heat treatment, dripping perovskite precursor solution, heat treatment again, coating hole transport layer, evaporation of metal electrodes and other processes (Minjin Kim et al. Science, 2022, 375 (6578): 302-306, Sara Pescetelli et al. Nature Energy, 2022, 7, 597-607). This process requires multiple high-temperature treatments, which not only has complex equipment and processes, high energy consumption, but also easily introduces new defects such as pores and cracks in the device, resulting in a decrease in device efficiency, which is not conducive to the production of large-area battery components. The team of the present invention reported in previous research a method for preparing a three-layer mesoporous carbon electrode perovskite solar cell, which includes coating mesoporous TiO2, first calcination, coating mesoporous ZrO2, coating mesoporous carbon electrode, second calcination, dripping perovskite precursor solution, heat treatment and other steps (see CN201810595109.2, CN202110273910.7, CN202310156226.X, etc.). This method solves the process problem of preparing perovskite solar cells over a large area, but still requires multiple heat treatments, and does not solve the problem of device defects and reduced efficiency. Summary of the invention
[0004] In response to the above defects or improvement needs of the prior art, the present invention provides a method for preparing printable mesoporous perovskite solar cells without the aid of high-temperature heat treatment and its application, the purpose of which is to provide a preparation method that can prepare mesoporous perovskite solar cells on a large area while reducing the need for heat treatment.
[0005] In order to achieve the above objectives, in a first aspect, the present invention provides a method for preparing a printable mesoporous perovskite solar cell without high temperature heat treatment, comprising:
[0006] Sequentially coating a perovskite-electron transport material mixed slurry, a perovskite-insulating material mixed slurry, a perovskite-bottom electrode material mixed slurry and a pure bottom electrode slurry on a conductive substrate; performing a leveling operation after coating each slurry, and performing a drying operation after the leveling operation is completed, or performing a drying operation at the same time as the coating and leveling operations, to obtain a perovskite-electron transport layer, a perovskite-insulating layer, a perovskite-bottom electrode layer and a bottom electrode stacked sequentially on the conductive substrate;
[0007] A back plate is added to the bottom electrode, a wire is connected, and a sealant is applied to obtain a mesoporous perovskite solar cell;
[0008] Among them, the perovskite-electron transport material mixed slurry is a slurry obtained by fully mixing the perovskite precursor solution, the electron transport material and the thickener; the perovskite-insulating material mixed slurry is a slurry obtained by fully mixing the perovskite precursor solution, the insulating material and the thickener; the perovskite-bottom electrode material mixed slurry is a slurry obtained by fully mixing the perovskite precursor solution, the bottom electrode material and the thickener; the pure bottom electrode slurry is a slurry obtained by fully mixing the bottom electrode material, the perovskite anti-solvent and the thickener.
[0009] Further preferably, in the perovskite-electron transport material mixed slurry, the electron transport material comprises an n-type semiconductor material, has an average particle size of 5 to 500 nm, and is used in an amount of 0.05 to 0.5 g per milliliter of the perovskite precursor solution;
[0010] In the perovskite-insulating material mixed slurry, the average particle size of the insulating material is 5 to 500 nm, and the amount used is 0.05 to 0.5 g per milliliter of the perovskite precursor solution;
[0011] The average particle size of the bottom electrode material in the perovskite-bottom electrode material mixed slurry is 5 to 500 nm, and the amount used is 0.05 to 0.5 g per milliliter of the perovskite precursor solution;
[0012] The average particle size of the bottom electrode material in the pure bottom electrode slurry is 5 to 500 nm, and the dosage is 0.1 to 1.0 g per milliliter of perovskite anti-solvent.
[0013] Further preferably, the electron transport material is TiO2, with an average particle size of 30 to 50 nm, and an amount of 0.1 to 0.2 g per milliliter of perovskite precursor solution.
[0014] Further preferably, the insulating material is ZrO2, the average particle size is 30-50 nm, and the amount used is 0.1-0.2 g per milliliter of perovskite precursor solution.
[0015] Further preferably, the bottom electrode material in the perovskite-bottom electrode material mixed slurry is a mixture of graphite and carbon black, and the amount used is 0.1-0.2 g per milliliter of perovskite precursor solution; wherein the average particle size of graphite is 5-10 μm, and the average particle size of carbon black is 30-50 nm.
[0016] Further preferably, the bottom electrode material in the pure bottom electrode slurry is a mixture of graphite and carbon black, and the amount used is 0.2-0.4 g per milliliter of perovskite antisolvent; wherein the average particle size of graphite is 5-10 μm, and the average particle size of carbon black is 30-50 nm.
[0017] Further preferably, the thickeners in the perovskite-electron transport material mixed slurry, the perovskite-insulating material mixed slurry and the perovskite-bottom electrode material mixed slurry all contain a polymer soluble in DMF, DMSO, NMF or GBL, and the average molecular weight is 10 2 ~10 6 , the added amount is 0.01-0.05 g per milliliter of perovskite precursor solution;
[0018] The thickener in the pure bottom electrode slurry contains a polymer dissolved in DMF, DMSO, NMF or GBL with an average molecular weight of 10 2 ~10 6 The amount added is 0.01 to 0.05 g per milliliter of perovskite antisolvent.
[0019] Further preferably, the thickener in the perovskite-electron transport material mixed slurry, the perovskite-insulating material mixed slurry and the perovskite-bottom electrode material mixed slurry is polyvinylidene fluoride with an average molecular weight of 10 3 ~10 4 , the added amount is 0.02-0.03 g per milliliter of perovskite precursor solution;
[0020] The thickener in the pure bottom electrode slurry is polyvinylidene fluoride with an average molecular weight of 10 3 ~10 4 The amount added is 0.02 to 0.05 g per milliliter of perovskite antisolvent.
[0021] Further preferably, the thickness of the perovskite-electron transport layer is 0.5-1.5 μm; the thickness of the perovskite-insulating layer is 2-3 μm; the thickness of the perovskite-bottom electrode layer is 0.5-1.5 μm; and the thickness of the bottom electrode is 20-30 μm.
[0022] In a second aspect, the present invention provides a printable mesoporous perovskite solar cell, which is prepared by the method for preparing a printable mesoporous perovskite solar cell provided by the first aspect of the present invention.
[0023] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects:
[0024] 1. The present invention provides a method for preparing a printable mesoporous perovskite solar cell without the aid of high-temperature heat treatment, wherein an electron transport material, an insulating material, and a bottom electrode material are directly mixed with a perovskite precursor solution, and a thickener is introduced to adjust the viscosity and leveling properties thereof, thereby obtaining a perovskite-electron transport material mixed slurry, a perovskite-insulating material mixed slurry, and a perovskite-bottom electrode material mixed slurry, which are sequentially coated on a conductive substrate; the film formation of functional layers such as an electron transport layer, an insulating layer, and a bottom electrode layer and the crystallization of perovskite can be achieved through coating, leveling, and drying operations, thereby eliminating the complicated coating and high-temperature calcination processes in the previous process of preparing large-area mesoporous perovskite solar cells, reducing the need for heat treatment, reducing energy consumption and costs, and also reducing defects in the device caused by thermal stress. The present invention is a method for preparing mesoporous perovskite solar cells on a large scale while reducing the need for heat treatment, and has good application potential for the preparation of large-area perovskite solar cells.
[0025] 2. The method for preparing printable mesoporous perovskite solar cells without the aid of high-temperature heat treatment provided by the present invention directly mixes the functional layer material, the perovskite precursor solution and the thickener to prepare a mixed slurry when preparing the functional layer. After coating, leveling and drying, the precipitated perovskite calcium grains are filled in the framework formed by the functional layer material. Compared with the existing method of first preparing the functional layer separately and then adding the perovskite precursor solution, the filling rate of the perovskite calcium grains in each functional layer in the present invention is higher, so that the contact surface defects between the perovskite and the electron transport layer and the electrode are less, the defect compounding loss is reduced, and it is beneficial to improve the photoelectric conversion efficiency of the battery.
[0026] 3. The method for preparing printable mesoporous perovskite solar cells provided by the present invention does not require high-temperature heat treatment and can be completed with the help of mixing, coating, heating and other processes, and does not require high-temperature heating, high vacuum and other processes, and the process is simple.
[0027] 4. The method for preparing printable mesoporous perovskite solar cells provided by the present invention does not require high-temperature heat treatment. Since the maximum heat treatment temperature does not exceed 150°C, which is lower than the decomposition temperature of perovskite, it is conducive to the preparation of perovskite materials with low defect density.
[0028] 5. The method for preparing printable mesoporous perovskite solar cells provided by the present invention does not require high-temperature heat treatment. Since there is no high-temperature heating process, the device does not need to be repeatedly subjected to high thermal stress, thereby reducing the probability of defects such as voids and cracks appearing inside the device and improving the yield rate.
[0029] 6. Furthermore, the present invention provides a method for preparing printable mesoporous perovskite solar cells without the aid of high-temperature heat treatment. In the perovskite-electron transport material mixed slurry, the electron transport material comprises an n-type semiconductor material with an average particle size of 5 to 500 nm, and the amount is 0.05 to 0.5 g per milliliter of perovskite precursor solution; in the perovskite-insulating material mixed slurry, the average particle size of the insulating material is 5 to 500 nm, and the amount is 0.05 to 0.5 g per milliliter of perovskite precursor solution; the average particle size of the bottom electrode material in the perovskite-bottom electrode material mixed slurry is 5 to 500 nm, and the amount is 0.05 to 0.5 g per milliliter of perovskite precursor solution; the average particle size of the bottom electrode material in the pure bottom electrode slurry is 5 to 500 nm, and the amount is 0.1 to 1.0 g per milliliter of perovskite anti-solvent. By designing the ratio of each component in the mixed slurry, the slurry has moderate viscosity and excellent leveling properties, which is conducive to coating, film formation and dispersion of nanoparticles, while avoiding problems such as difficulty in solvent evaporation and difficulty in perovskite crystallization caused by excessive use of solvent.
[0030] 7. Furthermore, in the method for preparing printable mesoporous perovskite solar cells without the aid of high-temperature heat treatment provided by the present invention, the thickness of the perovskite-electron transport layer is 0.5-1.5 μm; the thickness of the perovskite-insulating layer is 2-3 μm; the thickness of the perovskite-bottom electrode layer is 0.5-1.5 μm; the thickness of the bottom electrode is 20-30 μm; the above thickness design is beneficial for the perovskite material to fully absorb solar energy and increase output power, and is also beneficial for avoiding problems such as excessive resistance due to excessive film thickness, efficiency loss due to internal defects, and increased cost due to excessive materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic diagram of a preparation process of a printable mesoporous perovskite solar cell without high temperature heat treatment provided by an embodiment of the present invention;
[0032] Figure 2 The IV test results of the embodiments of the present invention and the comparative examples are shown in FIG. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0034] After analyzing the existing preparation methods of mesoporous perovskite solar cells, it is found that it is necessary to develop a process system that can prepare mesoporous perovskite solar cells on a large scale, while reducing the need for heat treatment, reducing energy consumption, and reducing device defects. The specific requirements are: ① The slurry of materials such as electron transport materials, insulating materials, and bottom electrode materials needs to be dried at a relatively low temperature (≤150°C as much as possible) to form a film; ② The slurry needs to have appropriate viscosity and leveling properties to ensure uniform film formation after coating; ③ The perovskite precursor solution can evenly penetrate into the nanofilm and precipitate perovskite crystals. To meet the above conditions, the perovskite precursor solution can be directly mixed with the slurry of materials such as electron transport materials, insulating materials or bottom electrode materials, and a small amount of thickener that does not need to be removed can be introduced to adjust its viscosity and leveling properties, so that a slurry that meets the requirements can be prepared. The solvents commonly used in perovskite precursor solutions, such as dimethylformamide (DMF), dimethyl sulfoxide (DMSO), n-methylformamide (NMF), and gamma-butyrolactone (GBL), have a low volatilization temperature. During the battery preparation process, the slurry can be directly coated on a substrate such as conductive glass, and the film formation of slurries of materials such as electron transport materials, insulating materials, and bottom electrode materials, the volatilization of the perovskite precursor solution, and the crystallization of the perovskite can be achieved simultaneously at a lower temperature.
[0035] Specifically, in order to achieve the above-mentioned objectives, in a first aspect, the present invention provides a method for preparing a printable mesoporous perovskite solar cell without high-temperature heat treatment, comprising:
[0036] Sequentially coating a perovskite-electron transport material mixed slurry, a perovskite-insulating material mixed slurry, a perovskite-bottom electrode material mixed slurry and a pure bottom electrode slurry on a conductive substrate; performing a leveling operation after coating each slurry, and performing a drying operation after the leveling operation is completed, or performing a drying operation at the same time as the coating and leveling operations, to obtain a perovskite-electron transport layer, a perovskite-insulating layer, a perovskite-bottom electrode layer and a bottom electrode stacked sequentially on the conductive substrate;
[0037] A back plate is added to the bottom electrode, a wire is connected, and a sealant is applied to obtain a mesoporous perovskite solar cell;
[0038] Among them, the perovskite-electron transport material mixed slurry is a slurry obtained by fully mixing the perovskite precursor solution, the electron transport material and the thickener; the perovskite-insulating material mixed slurry is a slurry obtained by fully mixing the perovskite precursor solution, the insulating material and the thickener; the perovskite-bottom electrode material mixed slurry is a slurry obtained by fully mixing the perovskite precursor solution, the bottom electrode material and the thickener; the pure bottom electrode slurry is a slurry obtained by fully mixing the bottom electrode material, the perovskite anti-solvent and the thickener.
[0039] Specifically, the solvent of the perovskite precursor solution includes one or more of DMF, DMSO, NMF, and GBL, preferably a 4:1 mixture of DMF / DMSO. The solute of the perovskite precursor solution is a perovskite precursor, and the composition is ABX3; wherein A includes one or more of methylamine, formamidine, Cs, and Rb; B includes a transition metal, which can be a mixture of one or more transition metals such as Pb and Sn; X includes one or more of I, Br, and Cl. ABX3 can directly use the ready-made ABX3 product, or it can be obtained by weighing AX and BX2 in proportion. A, B, and X can all deviate from the stoichiometric ratio of 1:1:3 within a certain range, and the deviation ratio is within ±20%. Preferably, 1 to 1.2 mmol of perovskite precursor should be added per milliliter of solvent.
[0040] It should be noted that the perovskite precursor solutions in the perovskite-electron transport material mixed slurry, the perovskite-insulating material mixed slurry and the perovskite-bottom electrode material mixed slurry may be the same or different, and there is no limitation here.
[0041] In an optional embodiment, in the perovskite-electron transport material mixed slurry, the electron transport material comprises an n-type semiconductor material, has an average particle size of 5 to 500 nm, and is used in an amount of 0.05 to 0.5 g per milliliter of the perovskite precursor solution;
[0042] In the perovskite-insulating material mixed slurry, the average particle size of the insulating material is 5 to 500 nm, and the amount used is 0.05 to 0.5 g per milliliter of the perovskite precursor solution;
[0043] The average particle size of the bottom electrode material in the perovskite-bottom electrode material mixed slurry is 5 to 500 nm, and the amount used is 0.05 to 0.5 g per milliliter of the perovskite precursor solution;
[0044] The average particle size of the bottom electrode material in the pure bottom electrode slurry is 5 to 500 nm, and the dosage is 0.1 to 1.0 g per milliliter of perovskite anti-solvent.
[0045] Further preferably, the electron transport material is TiO2, with an average particle size of 30 to 50 nm, and an amount of 0.1 to 0.2 g per milliliter of perovskite precursor solution.
[0046] In an optional embodiment, the thickeners in the perovskite-electron transport material mixed slurry, the perovskite-insulating material mixed slurry, and the perovskite-bottom electrode material mixed slurry all contain a polymer dissolved in DMF, DMSO, NMF or GBL, and the average molecular weight is 10 2 ~10 6 , the added amount is 0.01-0.05 g per milliliter of perovskite precursor solution;
[0047] The thickener in the pure bottom electrode slurry contains a polymer dissolved in DMF, DMSO, NMF or GBL with an average molecular weight of 10 2 ~10 6 The amount added is 0.01 to 0.05 g per milliliter of perovskite antisolvent.
[0048] In an optional embodiment, the thickness of the perovskite-electron transport layer is 0.5-1.5 μm; the thickness of the perovskite-insulating layer is 2-3 μm; the thickness of the perovskite-bottom electrode layer is 0.5-1.5 μm; and the thickness of the bottom electrode is 20-30 μm.
[0049] In an optional embodiment, the electron transport material comprises an n-type semiconductor material, such as one or more of TiO2, SnO2 and ZnO.
[0050] In an alternative embodiment, the insulating material includes one or more of ZrO2, SiO2 and MgO.
[0051] In an optional embodiment, the bottom electrode materials in the perovskite-bottom electrode material mixed slurry and the pure bottom electrode slurry both contain one or more of graphite, carbon black, carbon nanotubes and nano-metal fibers.
[0052] In an optional embodiment, the thickeners in the perovskite-electron transport material mixed slurry, the perovskite-insulating material mixed slurry, the perovskite-bottom electrode material mixed slurry and the pure bottom electrode slurry all contain polymers dissolved in DMF, DMSO, NMF or GBL.
[0053] It should be noted that the annealing temperature adopted in the method for preparing printable mesoporous perovskite solar cells provided by the present invention is 50 to 150°C, preferably 75 to 125°C; the drying time of the perovskite-electron transport layer, the perovskite-insulating layer and the perovskite-bottom electrode layer is preferably 15 to 30 minutes; the drying time of the pure bottom electrode layer is preferably 60 to 120 minutes; the design of the above temperature and drying time can ensure that the slurry is easily and fully evaporated and the perovskite is fully crystallized, while avoiding the problems of perovskite defect proliferation and efficiency reduction caused by excessive temperature and excessive drying time.
[0054] like Figure 1 As shown, the preparation process of the above-mentioned printable mesoporous perovskite solar cell preparation method is described in detail as follows:
[0055] Get perovskite-electron transport material mixed slurry, perovskite-insulating material mixed slurry, perovskite-bottom electrode material mixed slurry and pure bottom electrode slurry:
[0056] The perovskite-electron transport material mixed slurry, the perovskite-insulating material mixed slurry, the perovskite-bottom electrode material mixed slurry and the pure bottom electrode slurry are prepared by the following method:
[0057] a) For the preparation of the perovskite-electron transport material mixed slurry, the specific steps are: the perovskite precursor solution, the electron transport material, and the thickener are weighed in a certain proportion and then fully mixed to obtain the perovskite-electron transport material mixed slurry.
[0058] In an optional embodiment, the electron transport material comprises an n-type semiconductor material, which can be a mixture of one or more of TiO2, SnO2, ZnO, BaSnO3 or any other n-type semiconductor material, with an average particle size of 5 to 500 nm, and an amount of 0.05 to 0.5 g per milliliter of perovskite precursor solution. Preferably, the electron transport material is TiO2, SnO2, ZnO or BaSnO3. When the electron transport material is TiO2, SnO2 or ZnO, the average particle size of the electron transport material is 30 to 50 nm, and the amount is 0.1 to 0.2 g of electron transport material per milliliter of perovskite precursor solution. When the electron transport material is BaSnO3, the average particle size of the electron transport material is 15 to 30 nm, and the amount is 0.1 to 0.2 g of electron transport material per milliliter of perovskite precursor solution.
[0059] In an optional embodiment, the thickener in the perovskite-electron transport material mixed slurry comprises a polymer soluble in DMF, DMSO, NMF or GBL, which can be a mixture of one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyaniline (PAN), polypyrrole (PPy) or any other polymer soluble in DMF, DMSO, NMF or GBL, such as a mixture of one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyaniline and polypyrrole. The average molecular weight of the thickener is preferably 10 2 ~10 6, the amount added is 0.01 to 0.05 g per milliliter of perovskite precursor solution. Preferably, the thickener is polyvinylidene fluoride, polytetrafluoroethylene, polyaniline, polypyrrole or a copolymer of polyaniline and polypyrrole. When the thickener is polyvinylidene fluoride or polytetrafluoroethylene, the average molecular weight of the thickener is 1000 to 10000, and the amount added is 0.02 to 0.03 g of the thickener per milliliter of the perovskite precursor solution. When the thickener is polyaniline, polypyrrole or a copolymer of the two, the average molecular weight of the thickener is 1000 to 100000, and the amount added is 0.03 to 0.05 g of the thickener per milliliter of the perovskite precursor solution.
[0060] The mixing process used to prepare the perovskite-electron transport material mixed slurry can be a mixture of one or more of mechanical stirring, magnetic stirring, mechanical oscillation, ultrasonic oscillation or any other slurry mixing processes. When ultrasonic oscillation is used, the duration is preferably 30 minutes, and when other mixing processes are used, the duration is preferably 1 to 2 hours.
[0061] b) For the preparation of the perovskite-insulating material mixed slurry, the specific steps are: weighing the perovskite precursor solution, the insulating material, and the thickener according to a certain proportion and fully mixing them to obtain the perovskite-insulating material mixed slurry.
[0062] In an optional embodiment, the insulating material can be a mixture of one or more of ZrO2, SiO2, MgO, calcium silicate, magnesium silicate or any other insulating material, with an average particle size of 5 to 500 nm and an amount of 0.05 to 0.5 g per milliliter of perovskite precursor solution. Preferably, the insulating material is ZrO2, SiO2, MgO, calcium silicate or magnesium silicate. When the insulating material is ZrO2, SiO2 or MgO, the average particle size of the insulating material is 30 to 50 nm, and the amount is 0.1 to 0.2 g of the insulating material per milliliter of the perovskite precursor solution. When the insulating material is calcium silicate or magnesium silicate, the average particle size of the insulating material is 100 to 200 nm, and the amount is 0.1 to 0.2 g of the insulating material per milliliter of the perovskite precursor solution.
[0063] In an optional embodiment, the thickener in the perovskite-insulating material mixed slurry comprises a polymer soluble in DMF, DMSO, NMF or GBL, which can be a mixture of one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyaniline (PAN), polypyrrole (PPy) or any other polymer soluble in DMF, DMSO, NMF or GBL, such as a mixture of one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyaniline and polypyrrole. The average molecular weight of the thickener is preferably 10 2 ~10 6, the amount added is 0.01-0.05g per milliliter of perovskite precursor solution. Preferably, the thickener is polyvinylidene fluoride, the average molecular weight is 1000-10000, and the amount added is 0.02-0.03g of thickener per milliliter of perovskite precursor solution. Preferably, the thickener is polyvinylidene fluoride, polytetrafluoroethylene, polyaniline, polypyrrole or a copolymer of polyaniline and polypyrrole. When the thickener is polyvinylidene fluoride or polytetrafluoroethylene, the average molecular weight of the thickener is 1000-10000, and the amount added is 0.02-0.03g of thickener per milliliter of perovskite precursor solution. When the thickener is polyaniline, polypyrrole or a copolymer of the two, the average molecular weight of the thickener is 1000-100000, and the amount added is 0.03-0.05g of thickener per milliliter of perovskite precursor solution.
[0064] The mixing process used to prepare the perovskite-insulating material mixed slurry can be a mixture of one or more of mechanical stirring, magnetic stirring, mechanical oscillation, ultrasonic oscillation or any other slurry mixing processes. When ultrasonic oscillation is used, the duration is preferably 30 minutes, and when other mixing processes are used, the duration is preferably 1 to 2 hours.
[0065] c) For the preparation of the perovskite-bottom electrode material mixed slurry, the specific steps are: weighing the perovskite precursor solution, the bottom electrode material, and the thickener according to a certain proportion and fully mixing them to obtain the perovskite-bottom electrode material mixed slurry.
[0066] In an optional embodiment, the bottom electrode material in the perovskite-bottom electrode material mixed slurry can be a mixture of one or more of graphite, carbon black, carbon nanotubes, nanometal fibers or any other conductive materials, with an average particle size of 5 to 500 nm, and an amount of 0.05 to 0.5 g per milliliter of perovskite precursor solution. Preferably, the bottom electrode material in the perovskite-bottom electrode material mixed slurry is a 3:1 mixture of graphite and carbon black, a 3:1 mixture of graphite and carbon nanotubes, or a 3:1 mixture of graphite and nanometal fibers. When the bottom electrode material in the perovskite-bottom electrode material mixed slurry is a 3:1 mixture of graphite and carbon black, the average particle size of graphite is 5 to 10 μm, the average particle size of carbon black is 30 to 50 nm, and the amount is 0.1 to 0.2 g of bottom electrode material per milliliter of perovskite precursor solution. When the bottom electrode material in the perovskite-bottom electrode material mixed slurry is a 3:1 mixture of graphite and carbon nanotubes, or a 3:1 mixture of graphite and nano-metal fibers, the average particle size of the graphite is 5 to 10 μm, the average diameter of the carbon nanotubes or nano-metal fibers is 30 to 50 nm, and the length is 1 to 10 μm. The dosage is 0.1 to 0.2 g of bottom electrode material per milliliter of perovskite precursor solution.
[0067] In an optional embodiment, the thickener in the perovskite-bottom electrode material mixed slurry comprises a polymer soluble in DMF, DMSO, NMF or GBL, which can be a mixture of one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyaniline (PAN), polypyrrole (PPy) or any other polymer soluble in DMF, DMSO, NMF or GBL, such as a mixture of one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyaniline and polypyrrole. The average molecular weight of the thickener is preferably 10 2 ~10 6 , the amount added is 0.01-0.05g per milliliter of perovskite precursor solution. Preferably, the thickener is polyvinylidene fluoride, the average molecular weight is 1000-10000, and the amount added is 0.02-0.03g of thickener per milliliter of perovskite precursor solution. Preferably, the thickener is polyvinylidene fluoride, polytetrafluoroethylene, polyaniline, polypyrrole or a copolymer of polyaniline and polypyrrole. When the thickener is polyvinylidene fluoride or polytetrafluoroethylene, the average molecular weight of the thickener is 1000-10000, and the amount added is 0.02-0.03g of thickener per milliliter of perovskite precursor solution. When the thickener is polyaniline, polypyrrole or a copolymer of the two, the average molecular weight of the thickener is 1000-100000, and the amount added is 0.03-0.05g of thickener per milliliter of perovskite precursor solution.
[0068] The mixing process used to prepare the perovskite-bottom electrode material mixed slurry can be a mixture of one or more of mechanical stirring, magnetic stirring, mechanical oscillation, ultrasonic oscillation or any other slurry mixing processes. When ultrasonic oscillation is used, the duration is preferably 30 minutes, and when other mixing processes are used, the duration is preferably 1 to 2 hours.
[0069] It should be noted that the components and amounts of the perovskite precursors, the components and amounts of the solvents and thickeners, and the mixing processes in a), b), and c) are not necessarily the same.
[0070] d) For the preparation of pure bottom electrode slurry, the specific steps are: weigh the bottom electrode material, perovskite anti-solvent, and thickener according to a certain proportion and fully mix them to obtain the pure bottom electrode slurry.
[0071] In an optional embodiment, the bottom electrode material in the pure bottom electrode slurry can be a mixture of one or more of graphite, carbon black, carbon nanotubes, nanometal fibers or any other conductive materials, with an average particle size of 5 to 500 nm, and an amount of 0.1 to 1.0 g per milliliter of perovskite antisolvent. Preferably, the bottom electrode material in the pure bottom electrode slurry is a 3:1 mixture of graphite and carbon black, a 3:1 mixture of graphite and carbon nanotubes, or a 3:1 mixture of graphite and nanometal fibers. When the bottom electrode material in the pure bottom electrode slurry is a 3:1 mixture of graphite and carbon black, the average particle size of graphite is 5 to 10 μm, the average particle size of carbon black is 30 to 50 nm, and the amount is 0.2 to 0.4 g of bottom electrode material per milliliter of perovskite antisolvent. When the bottom electrode material in the perovskite-bottom electrode material mixed slurry is a 3:1 mixture of graphite and carbon nanotubes, or a 3:1 mixture of graphite and nanometal fibers, the average particle size of the graphite is 5 to 10 μm, the average diameter of the carbon nanotubes or nanometal fibers is 30 to 50 nm, and the length is 1 to 10 μm. The amount used is 0.2 to 0.4 g of bottom electrode material per milliliter of perovskite anti-solvent.
[0072] It should be noted that the perovskite anti-solvent is a liquid that does not dissolve perovskite but can promote the crystallization of perovskite, and can be a mixture of one or more of chlorobenzene, bromobenzene, isopropanol or any other perovskite anti-solvents, preferably isopropanol.
[0073] In an optional embodiment, the thickener in the pure bottom electrode slurry comprises a polymer soluble in DMF, DMSO, NMF or GBL, which can be a mixture of one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyaniline (PAN), polypyrrole (PPy) or any other polymer soluble in DMF, DMSO, NMF or GBL, such as a mixture of one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyaniline and polypyrrole. The average molecular weight of the thickener is preferably 10 2 ~10 6 , the amount added is 0.01 to 0.05 g per milliliter of perovskite antisolvent. Preferably, the thickener is polyvinylidene fluoride, polytetrafluoroethylene, polyaniline, polypyrrole or a copolymer of polyaniline and polypyrrole. When the thickener is polyvinylidene fluoride or polytetrafluoroethylene, the average molecular weight of the thickener is 1000 to 10000, and the amount added is 0.02 to 0.03 g of the thickener per milliliter of the perovskite antisolvent. When the thickener is polyaniline, polypyrrole or a copolymer of the two, the average molecular weight of the thickener is 1000 to 100000, and the amount added is 0.03 to 0.05 g of the thickener per milliliter of the perovskite antisolvent.
[0074] The mixing process used to prepare the pure bottom electrode slurry can be a mixture of one or more of mechanical stirring, magnetic stirring, mechanical oscillation, ultrasonic oscillation or any other slurry mixing processes. When ultrasonic oscillation is used, the duration is preferably 30 minutes, and when other mixing processes are used, the duration is preferably 1 to 2 hours.
[0075] It should be particularly pointed out that the composition and amount of the bottom electrode material, the composition and amount of the thickener, and the mixing process in steps c) and d) are not necessarily the same.
[0076] After coating of each slurry, a leveling operation is performed, and after the leveling operation, a drying operation is performed, or a drying operation is performed simultaneously during coating and leveling operations, to obtain a perovskite-electron transport layer, a perovskite-insulating layer, a perovskite-bottom electrode layer and a bottom electrode stacked in sequence on a conductive substrate;
[0077] It should be noted that drying can be carried out separately after coating and leveling are completed, or it can be carried out simultaneously with coating and leveling, or it can be carried out simultaneously with coating and leveling steps and continue after leveling is completed.
[0078] e) Preparation of perovskite-electron transport layer:
[0079] The specific steps are: coating a perovskite-electron transport material mixed slurry on a conductive substrate, and waiting for the slurry to be leveled and dried to obtain a perovskite-electron transport layer.
[0080] It should be noted that the conductive substrate is a transparent material with a surface conductive layer, and in an optional embodiment, it can be FTO glass, ITO glass, or ITO-coated flexible plastic film, or any other transparent material with a surface conductive layer. The conductive substrate can be a commercial conductive substrate purchased directly, or a conductive substrate with other functional layers coated on the surface.
[0081] The coating can be a combination of screen printing, slit coating, wire rod coating, ultrasonic spray coating or any other slurry coating process, preferably slit coating. The final film thickness of the perovskite-electron transport material mixed slurry (the thickness of the perovskite-electron transport layer) is preferably 0.5 to 1.5 μm.
[0082] The leveling method may be natural leveling, ultrasonic assisted leveling, high pressure nitrogen gas flow assisted leveling or any other slurry leveling method; preferably, natural leveling is adopted, and the duration is 15 to 30 minutes.
[0083] The drying operation temperature is 50-150°C, and can be heating drying, blast drying, vacuum drying or any other drying method that can be used to evaporate the solvent (DMF, DMSO, NMF or GBL) in the slurry of the present invention; preferably, heating drying is adopted, the temperature is 75-125°C, and the duration is 15-30min.
[0084] f) Preparation of perovskite-insulating layer:
[0085] The specific steps are: coating a perovskite-insulating material mixed slurry on the perovskite-electron transport layer, and waiting for the slurry to be leveled and dried to obtain a perovskite-insulating layer.
[0086] It should be noted that the coating can be a combination of one or more of screen printing, slit coating, wire rod coating, ultrasonic spraying or any other slurry coating process, preferably slit coating. The final film thickness of the perovskite-insulating material mixed slurry (the thickness of the perovskite-insulating layer) is preferably 2 to 3 μm.
[0087] The leveling method may be natural leveling, ultrasonic assisted leveling, high pressure nitrogen gas flow assisted leveling or any other slurry leveling method; preferably, natural leveling is adopted, and the duration is 15 to 30 minutes.
[0088] The drying operation temperature is 50-150°C, and can be heating drying, blast drying, vacuum drying or any other drying method that can be used to evaporate the solvent (DMF, DMSO, NMF or GBL) in the slurry of the present invention; preferably, heating drying is adopted, the temperature is 75-125°C, and the duration is 15-30min.
[0089] g) Preparation of perovskite-bottom electrode layer:
[0090] The specific steps are: coating a mixed slurry of perovskite-bottom electrode materials on the perovskite-insulating layer, and waiting for the slurry to be leveled and dried to obtain a perovskite-bottom electrode layer.
[0091] It should be noted that the coating can be a combination of one or more of screen printing, slit coating, wire rod coating, ultrasonic spraying or any other slurry coating process, preferably slit coating. The final film thickness of the perovskite-bottom electrode material mixed slurry (the thickness of the perovskite-bottom electrode layer) is preferably 0.5 to 1.5 μm.
[0092] The leveling method may be natural leveling, ultrasonic assisted leveling, high pressure nitrogen gas flow assisted leveling or any other slurry leveling method; preferably, natural leveling is adopted, and the duration is 15 to 30 minutes.
[0093] The drying operation temperature is 50-150°C, and can be heating drying, blast drying, vacuum drying or any other drying method that can be used to evaporate the solvent (DMF, DMSO, NMF or GBL) in the slurry of the present invention; preferably, heating drying is adopted, the temperature is 75-125°C, and the duration is 15-30min.
[0094] h) Preparation of bottom electrode:
[0095] The specific steps are: coating a pure bottom electrode slurry on the perovskite-bottom electrode layer, and waiting for the slurry to be leveled and dried to obtain a pure bottom electrode layer.
[0096] It should be noted that the coating can be a combination of screen printing, slit coating, wire rod coating, ultrasonic spraying or any other slurry coating process, preferably slit coating. The final film thickness of the pure bottom electrode slurry (the thickness of the bottom electrode layer) is preferably 20 to 30 μm.
[0097] The leveling method may be natural leveling, ultrasonic assisted leveling, high pressure nitrogen gas flow assisted leveling or any other slurry leveling method; preferably, natural leveling is adopted, and the duration is 15 to 30 minutes.
[0098] The drying operation temperature is 50-150°C, preferably 80°C, and can be heating drying, blast drying, vacuum drying or any other drying method that can be used to evaporate the anti-solvent (chlorobenzene, bromobenzene or isopropanol, etc.) in the slurry of the present invention; preferably, heating drying is adopted, the temperature is 75-125°C, and the duration is 60-120min.
[0099] i) Packaging and cooling to obtain the final device:
[0100] The specific steps are: adding a back plate on the bottom electrode of the device obtained in h), connecting wires, and applying sealant to obtain a perovskite solar cell.
[0101] In an optional implementation, the back panel is made of an airtight plate, such as glass, organic glass or other airtight plates.
[0102] The present invention has no special limitation on the method of connecting the wires, and the method of connecting the wires well known to those skilled in the art can be used; the sealant can be commercial sealant, and common ingredients are epoxy resin or ethylene-vinyl acetate copolymer.
[0103] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.
[0104] In order to further illustrate the method for preparing a printable mesoporous perovskite solar cell without high-temperature heat treatment provided by the present invention, it is described in detail below in conjunction with specific embodiments, but it should not be understood as limiting the scope of protection of the present invention.
[0105] Example 1
[0106] This embodiment provides a MA-based 0.4 FA 0.6 A method for preparing a perovskite solar cell made of PbI3 perovskite material.
[0107] In this embodiment, the battery device uses FTO glass coated with a dense TiO2 film as a conductive substrate, wherein the average thickness of the FTO layer is 300 nm, and the average thickness of the dense TiO2 layer is 20 nm.
[0108] The perovskite precursor solution is always MA 0.4 FA 0.6 PbI3 was used as the solute. The weighing method was to weigh and mix MAI, FAI, and PbI2 in a ratio of 0.4:0.6:1. A 4:1 mixture of DMF / DMSO was used as the solvent. 1.2 mmol MA was added per milliliter of solvent. 0.4 FA 0.6 PbI3, and magnetic stirring for 1 hour to obtain the desired perovskite precursor solution.
[0109] During the slurry preparation process, the electron transport material used is TiO2 with an average particle size of 30nm, and the dosage is 0.1g per milliliter of precursor solution; the insulating material is ZrO2 with an average particle size of 30nm, and the dosage is 0.1g per milliliter of precursor solution; the conductive material is a 3:1 mixture of graphite with an average particle size of 6μm and carbon black with an average particle size of 30nm, and the dosage in the perovskite-bottom electrode material mixed slurry is 0.1g per milliliter of precursor solution, and the dosage in the pure bottom electrode slurry is 0.3g per milliliter of anti-solvent.
[0110] The thickener is always PVDF with a molecular weight of 10,000. The dosage in the mixed slurry of perovskite-electron transport material / insulating material / bottom electrode material is 0.025 g per milliliter of precursor solution, and the dosage in the pure bottom electrode slurry is 0.05 g per milliliter of anti-solvent.
[0111] The coating of perovskite-electron transport material mixed slurry, perovskite-insulating material mixed slurry, and perovskite-bottom electrode material mixed slurry was carried out by ultrasonic spraying, and the average coating thickness was 1μm / 2μm / 2μm respectively; the pure bottom electrode slurry was prepared by screen printing, and the average coating thickness was 25μm. Drying was carried out continuously during the coating / screen printing, leveling process, and after leveling, and heating drying was adopted. The drying temperature of the perovskite-electron transport material / insulating material / bottom electrode material mixed slurry was 85℃, and the duration was 30min; the drying temperature of the pure bottom electrode material mixed slurry was 100℃, and the duration was 90min.
[0112] Example 2
[0113] This embodiment provides a MA based on gradient doping. 0.4 FA 0.6 PbI 3-x Br x Method for preparing perovskite solar cells using perovskite materials.
[0114] The difference between this embodiment and embodiment 1 is that:
[0115] In the perovskite-electron transport material mixed slurry, the perovskite precursor solution is prepared by MA 0.4 FA 0.6 PbBr3 is used as the solute to achieve a doping effect in which the Br element presents a gradient decrease from the TiO2 layer to the bottom electrode layer in the final device.
[0116] Other material components, processing methods and steps are the same as those in Example 1.
[0117] Example 3
[0118] The difference between this embodiment and embodiment 1 is that the electron transport material used is SnO2 with an average particle size of 50nm, and the dosage is 0.1g per milliliter of precursor solution; the insulating material is SiO2 with an average particle size of 50nm, and the dosage is 0.1g per milliliter of precursor solution; the conductive material is a 3:1 mixture of graphite with an average particle size of 6μm and carbon nanotubes with an average diameter of 50nm, and the dosage in the perovskite-bottom electrode material mixed slurry is 0.1g per milliliter of precursor solution; the thickener is always polypyrrole with a molecular weight of 20,000, and the dosage in the perovskite-electron transport material / insulating material / bottom electrode material mixed slurry is 0.025g per milliliter of precursor solution, and the dosage in the pure bottom electrode slurry is 0.05g per milliliter of anti-solvent.
[0119] Comparative Example 1
[0120] The difference between this comparative example and Example 1 is that the perovskite solute in the perovskite-electron transport material / insulating material / bottom electrode material mixed slurry is removed to obtain a pure electron transport material / insulating material / bottom electrode material slurry; the coating sequence is the same as that in Example 1, and a blank device without perovskite is obtained after coating and drying; then, 4 μl of a perovskite precursor solution (having the same composition as the perovskite precursor solution in Example 1) is dripped onto the blank device, and after the solution completely penetrates into the blank device, the device is dried at 85° C. for 180 min to obtain the final device.
[0121] The performance tests of Examples 1, 2, 3 and Comparative Example 1 were conducted using a sunlight simulation light source (irradiance 1 kW / m 2 ) was used to test its open circuit voltage, short circuit current and photoelectric conversion efficiency using the IV test method, and the results were as follows: Figure 2 And the results shown in Table 1; Among them, Figure 2 1 is the IV test results of the embodiments and comparative examples of the present invention; Table 1 is the electrical properties of the perovskite solar cells obtained in the embodiments and comparative examples.
[0122] Table 1 shows the electrical properties of the perovskite solar cells obtained in the above examples and comparative examples.
[0123] Table 1 Performance test results of Examples 1, 2, 3 and Comparative Example 1
[0124]
[0125]
[0126] From Table 1 and Figure 2 It can be seen that by adopting the preparation method provided by the present invention and using different materials, the battery devices prepared have higher voltage, current and photoelectric conversion efficiency, which have significant advantages over the comparative examples.
[0127] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a printable mesoporous perovskite solar cell without high temperature heat treatment, characterized in that: include: sequentially coating a perovskite-electron transport material mixed slurry, a perovskite-insulating material mixed slurry, a perovskite-bottom electrode material mixed slurry and a pure bottom electrode slurry on a conductive substrate; After coating of each slurry, a leveling operation is performed, and after the leveling operation is completed, a drying operation is performed, or a drying operation is performed simultaneously during coating and leveling operations, to obtain a perovskite-electron transport layer, a perovskite-insulating layer, a perovskite-bottom electrode layer and a bottom electrode stacked in sequence on the conductive substrate; A back plate is added to the bottom electrode, a wire is connected, and a sealant is applied to obtain a mesoporous perovskite solar cell; Among them, the perovskite-electron transport material mixed slurry is a slurry obtained by fully mixing a perovskite precursor solution, an electron transport material and a thickener; the perovskite-insulating material mixed slurry is a slurry obtained by fully mixing a perovskite precursor solution, an insulating material and a thickener; the perovskite-bottom electrode material mixed slurry is a slurry obtained by fully mixing a perovskite precursor solution, a bottom electrode material and a thickener; the pure bottom electrode slurry is a slurry obtained by fully mixing a bottom electrode material, a perovskite anti-solvent and a thickener.
2. The method for preparing a printable mesoporous perovskite solar cell according to claim 1, characterized in that: In the perovskite-electron transport material mixed slurry, the electron transport material comprises an n-type semiconductor material, has an average particle size of 5 to 500 nm, and is used in an amount of 0.05 to 0.5 g per milliliter of perovskite precursor solution; In the perovskite-insulating material mixed slurry, the average particle size of the insulating material is 5 to 500 nm, and the amount used is 0.05 to 0.5 g per milliliter of perovskite precursor solution; The average particle size of the bottom electrode material in the perovskite-bottom electrode material mixed slurry is 5 to 500 nm, and the amount used is 0.05 to 0.5 g per milliliter of the perovskite precursor solution; The average particle size of the bottom electrode material in the pure bottom electrode slurry is 5 to 500 nm, and the dosage is 0.1 to 1.0 g per milliliter of perovskite anti-solvent.
3. The method for preparing a printable mesoporous perovskite solar cell according to claim 2, characterized in that: The electron transport material is TiO2, with an average particle size of 30 to 50 nm, and a dosage of 0.1 to 0.2 g per milliliter of perovskite precursor solution.
4. The method for preparing a printable mesoporous perovskite solar cell according to claim 2, characterized in that: The insulating material is ZrO2, the average particle size is 30-50 nm, and the dosage is 0.1-0.2 g per milliliter of perovskite precursor solution.
5. The method for preparing a printable mesoporous perovskite solar cell according to claim 2, characterized in that: The bottom electrode material in the perovskite-bottom electrode material mixed slurry is a mixture of graphite and carbon black, and the dosage is 0.1-0.2 g per milliliter of perovskite precursor solution; wherein the average particle size of the graphite is 5-10 μm, and the average particle size of the carbon black is 30-50 nm.
6. The method for preparing a printable mesoporous perovskite solar cell according to claim 2, characterized in that: The bottom electrode material in the pure bottom electrode slurry is a mixture of graphite and carbon black, and the dosage is 0.2-0.4 g per milliliter of perovskite anti-solvent; wherein the average particle size of the graphite is 5-10 μm, and the average particle size of the carbon black is 30-50 nm.
7. The method for preparing a printable mesoporous perovskite solar cell according to claim 2, characterized in that: The thickeners in the perovskite-electron transport material mixed slurry, the perovskite-insulating material mixed slurry, and the perovskite-bottom electrode material mixed slurry all contain a polymer soluble in DMF, DMSO, NMF or GBL, and have an average molecular weight of 10 2 ~10 6 , the added amount is 0.01-0.05 g per milliliter of perovskite precursor solution; The thickener in the pure bottom electrode slurry comprises a polymer soluble in DMF, DMSO, NMF or GBL, and has an average molecular weight of 10 2 ~10 6 The amount added is 0.01 to 0.05 g per milliliter of perovskite antisolvent.
8. The method for preparing a printable mesoporous perovskite solar cell according to claim 7, characterized in that: The thickeners in the perovskite-electron transport material mixed slurry, the perovskite-insulating material mixed slurry and the perovskite-bottom electrode material mixed slurry are all polyvinylidene fluoride with an average molecular weight of 10 3 ~10 4 , the added amount is 0.02-0.03 g per milliliter of perovskite precursor solution; The thickener in the pure bottom electrode slurry is polyvinylidene fluoride with an average molecular weight of 10 3 ~10 4 The amount added is 0.02 to 0.05 g per milliliter of perovskite antisolvent.
9. The method for preparing a printable mesoporous perovskite solar cell according to any one of claims 1 to 8, characterized in that: The thickness of the perovskite-electron transport layer is 0.5-1.5 μm; the thickness of the perovskite-insulating layer is 2-3 μm; the thickness of the perovskite-bottom electrode layer is 0.5-1.5 μm; and the thickness of the bottom electrode is 20-30 μm.
10. A printable mesoporous perovskite solar cell, characterized in that: The printable mesoporous perovskite solar cell is prepared by the method for preparing the printable mesoporous perovskite solar cell according to any one of claims 1 to 9.
Citation Information
Patent Citations
Production method of solar cell
CN110581223A
Single-carrier porous membrane scaffold and preparation method and application thereof
CN112919404A
Conductive paste, preparation method thereof and application of conductive paste in porous back electrode
CN116313219A
Perovskite solar cell and preparation method thereof
CN115498119A
Mesoporous perovskite solar cell and preparation method thereof
CN117320465A